FAKTOR-FAKTOR YANG MENENTUKAN KEPUASAN TAMU MENGINAP DI THE SAMAYA VILLA SEMINYAK - Ni Kadek Indah Septijayanthi; Ni Made Hartini (Journal Research of Management, 2021)
This study aims to determine what factors determine the satisfaction of guests staying at The Samaya Villa. Design This study uses a quantitative descriptive analysis that uses 100 respondents with a purposive sampling method. The analysis technique of this research is factor analysis. Data collection techniques with interviews, documentation, questionnaires. The results of this study indicate that 19 independent variables can be analyzed, rotated by factors so that there are two main components. The naming of the new factors is determined according to the variables that make up the factor. The first factor is the service quality factor which has the highest eigenvalue value of 9,280 and is able to explain the total variance of 48.844%. The second factor is the price factor which has the highest eigenvalue value of 4.408 and with a variance value of 23,200%. Implications for the company to always maintain the quality of service and product quality they have.